Corruption as a Deviant Social Attitude - István Takács
Corruption is a specific field of cooperation between social sectors. Corruption is a deviant behaviour, which can be traced back to several causes: the nature of economic and social regime as well as cultural aspects. The aim of corruption is to obtain advantages. The private advantages, however, are usually accompanied by significant social disadvantages. Corrupt behaviour often becomes a social norm. This paper analyses corruption as a deviant social attitude. Examining the countries of the Central Eastern European region, it states that they are moderately infected with corruption, which requires a national strategy against corruption and the establishment of institutional conditions for the implementation of the strategy. The paper underlines that corruption should be addressed not only within a national framework, it is also necessary to build up close co-operation among countries belonging to the same socio-economic system.integrity, norm, bribery, State Audit Office, public funds